Jovens (e) programadores(as) : uma abordagem geracional sobre a relação entre juventude e trabalho no contexto digital - Losekan, Gabriela (2022)
Currently, while young people are used to handling information and communication technologies (ICTs) and also benefit from the opportunities that arise from this digital context, they are more vulnerable to the impacts of economic and ongoing policies that directly reflect on their choices, experiences and projections from the labor field. In this context, programming as work has become an attractive profession for young people, either because of the promise of “the best jobs” or because of the technological, creative and flexible nature of this work. Thus, this research aimed to understand the generational relationship between the meanings of trajectories, experiences and lifestyles, imbricated in digital technologies, and work with programming for young people, as well as the reflection of this relationship in the formation of their individual and collective identities as young programmers. To achieve that, I interviewed young people, between 18 and 29 years old, professional and enthusiast programmers and attended to the Python Brazil 2021 Conference, an anual event organized by volunteers from the Python community in Brazil. The discussion based on the data collection shows that, although immersed in a new work culture, characterized from a context of reorganization, flexibility and precariousness of work relations, these young programmers make use of their own digital experiences to imprint other meanings on that same culture, changing, adapting or accepting certain patterns of behavior, which ends up reflecting on the way they attribute meaning to programming as work, organize themselves among peers and other aspects